201 Impact of Steam-Flaked Rye Fed in Combination with Steam-Flaked Corn on Performance and Carcass Characteristics of Yearling Steers. (12th April 2022) - Wagner, Samantha K; Erickson, Galen E; Troyer, Braden; McPhillips, Levi J; Brattain, Rebecca S
Abstract: The objective of this study was to evaluate the effects of increasing inclusions of steam-flaked hybrid rye (SFR) replacing steam-flaked corn (SFC) in finishing diets on cattle performance and carcass quality. Rye was grown as one hybrid and processed at a single feedyard in eastern Nebraska (14.5 kg/bu for SFR, 2.55 ± 0.94 mm average particle size). Crossbred yearling steers (n = 400, initial BW = 400 ± 24 kg) were used in a randomized block design (blocked by BW and source), stratified, and assigned randomly to pen (n = 40), and pen assigned randomly to treatment. Four treatments were evaluated, a control with no SFR (0%), and 3 inclusions of SFR where the rye replaced 25%, 50%, or 100% of the SFC in the diet (0%, 15.4%, 30.8%, and 60% SFR respectively). A linear decrease in carcass weight, dry matter intake, average daily gain (ADG), and gain:feed (G:F) was observed as SFR inclusion increased in the diet ( P ≤ 0.01). Intake decreased by 1.2 kg/d as SFR increased from 0 to 100% of the grain inclusion. A 14.5% reduction in ADG and 6.2% decrease in G:F was observed as SFR replaced SFC, which lead to decreases in calculated NEm and NEg dietary energy values based on performance. Longissimus muscle area ( P ≤ 0.01), 12 th rib fat ( P ≤ 0.03), and marbling score ( P ≤ 0.01) decreased linearly with increasing rye inclusion. Calculated yield grade did not differ among treatments ( P = 0.16). These data suggest no evidence of an associative effect for blending SFR with SFC. Based on dietary energy calculated using performance, SFR has approximately 92% the energy value of steam-flaked corn. Feeding flaked rye grain decreased intake, gain and feed efficiency suggesting SFR contains less energy than steam-flaked corn.